Thermoregulation-Focused Implementation of Delayed Cord Clamping among <34 Weeks' Gestational Age Neonates - Orton, Melissa; Theilen, Lauren; Clark, Erin; Baserga, Mariana; Lauer, Sarah; Ou, Zhining; Presson, Angela P.; Dupont, Tara; Katheria, Anup; Singh, Yogen; Chan, Belinda (American Journal of Perinatology, 2023)
Objective Delayed cord clamping (DCC) is recommended for all neonates; however, adapting such practice can be slow or unsustainable, especially among preterm neonates. During DCC neonates are exposed to a cool environment, raising concerns for neonatal hypothermia. Moderate hypothermia may induce morbidities that counteract the potential benefits of DCC. A quality improvement project on a thermoregulation-focused DCC protocol was implemented for neonates less than 34 weeks' gestational age (GA). The aim was to increase the compliance rate of DCC while maintaining normothermia.Study Design The DCC protocol was implemented on October 1, 2020 in a large Level III neonatal intensive care unit. The thermoregulation measures included increasing delivery room temperature and using heat conservation supplies (sterile polyethylene suit, warm towels, and thermal pads). Baseline characteristics, the compliance rate of DCC, and admission temperatures were compared 4 months' preimplementation and 26 months' postimplementationResults The rate of DCC increased from 20% (11/54) in preimplementation to 57% (240/425) in postimplementation (p < 0.001). The balancing measure of admission normothermia remained unchanged. In a postimplementation subgroup analysis, the DCC cohort had less tendency to experience admission moderate hypothermia (<36°C; 9.2 vs. 14.1%, p = 0.11). The DCC cohort had more favorable secondary outcomes including higher admission hematocrit, less blood transfusions, less intraventricular hemorrhage, and lower mortality. Improving the process measure of accurate documentation could help to identify implementation barriers.Conclusion Performing DCC in preterm neonates was feasible and beneficial without increasing admission hypothermia.Key Points
Keywords: delayed cord clamping; thermoregulation; quality improvement; prematurity; hypothermia